Abstracts Accepted for Publication 2017
DOI: 10.1136/annrheumdis-2017-eular.4008
|View full text |Cite
|
Sign up to set email alerts
|

AB1018 Detection of ANTI-DFS70 antibodies by indirect immunofluorescence (IIF) on novel HEP-2/DFS70-KO substrate for discriminating antinuclear antibodies (ANA) – positive healthy individuals (HI) and patients with systemic lupus erythematosus (SLE)

Abstract: BackgroundAutoantibodies against intracellular antigens are a serological hallmark of ANA-associated systemic autoimmune rheumatic diseases (AARD) such as SLE. IIF on HEp-2 cells for ANA remains the “gold standard” but it has very low positive predictive value. Up to 20% of serum samples from HI have been reported to have a positive ANA IIF test, the majority of them due to the presence of anti-dense fine speckled 70 (anti-DFS70) antibodies. Monospecific anti-DFS70 antibodies represent a biomarker that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Among ANA-positive healthy individuals, the frequency of isolated detection of antibodies to anti-DFS70 was 57%. The authors concluded that monospecific antibodies to anti-DFS70 serve as a negative serological marker for SLE [62]. However, in some studies, an assessment of their potential association with serological and clinical manifestations and disease activity has been conducted.…”
Section: Author Number Of Cases Conclusionmentioning
confidence: 99%
“…Among ANA-positive healthy individuals, the frequency of isolated detection of antibodies to anti-DFS70 was 57%. The authors concluded that monospecific antibodies to anti-DFS70 serve as a negative serological marker for SLE [62]. However, in some studies, an assessment of their potential association with serological and clinical manifestations and disease activity has been conducted.…”
Section: Author Number Of Cases Conclusionmentioning
confidence: 99%
“…[6], cancers (e.g., prostate cancer, breast cancer, etc.) [7,8] and healthy individuals (HI) [6, [9][10][11][12][13][14][15][16][17]. As an antinuclear autoantibody (ANA), most studies have focused on the clinical association between anti-DFS70 and systemic autoimmune rheumatic diseases (SARD) [6, 14,18], reporting that anti-DFS70 prevalence is comparable in SARD and in HI [19] unlike other autoantibodies which are common in different types of SARD.…”
Section: Introductionmentioning
confidence: 99%